Principle of entrepreneurship (ENT530) business model canvas: WT Scarf Collection / Nurul Shazwani Mohd Shukri - Mohd Shukri, Nurul Shazwani (2020)
WT Scarf is a new brand that provide a good fabric of bawal scarf to all the peoples especially bawal lovers. So that, we choose the best fabric and various of colours to attract the peoples to buy our product. Our product is focus on quality rather than quantity because the peoples always find the quality of the product. The best product will give customers feel more satisfaction and they will repeat order in other time